Targeting TREM2 for Parkinson’s Disease: Where to Go? - Li, Xiao-xian; Zhang, Feng (Frontiers in Immunology, 2021)
Parkinson’s disease (PD) is one of most common neurodegenerative disorders caused by a combination of environmental and genetic risk factors. Currently, numerous population genetic studies have shown that polymorphisms in myeloid cell-triggered receptor II (TREM2) are associated with a variety of neurodegenerative disorders. Recently, TREM2 has been verified to represent a promising candidate gene for PD susceptibility and progression. For example, the expression of TREM2 was apparently increased in the prefrontal cortex of PD patients. Moreover, the rare missense mutations in TREM2 (rs75932628, p.R47H) was confirmed to be a risk factor of PD. In addition, overexpression of TREM2 reduced dopaminergic neurodegeneration in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine mouse model of PD. Due to the complex pathogenesis of PD, there is still no effective drug treatment. Thus, TREM2 has received increasing widespread attention as a potential therapeutic target. This review focused on the variation of TREM2 in PD and roles of TREM2 in PD pathogenesis, such as excessive-immune inflammatory response, α-Synuclein aggregation and oxidative stress, to further provide evidence for new immune-related biomarkers and therapies for PD.